Efektivitas Pengelolaan Alokasi Dana Desa (Add) dalam Pembangunan Desa Bagon Kecamatan Puger Kabupaten Jember - Alwi Alkaff; Abdul Adim (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam Jember, 2022)
This study aims to determine the Effectiveness of Village Fund Allocation Management (ADD) in Village Development in Bagon Village, Puger District, Jember Regency. This research also explains what developments have been realized and what impacts it has on the community. In this research, the method taken is using the purposive sampling method, which is a sampling technique by determining certain criteria and determining the population according to the study and also determining the number of samples to be taken from the population. While the data collected in this study used the interview method, observation method, documentation, literature study, data validity techniques, observation persistence, participation extension and triangulation. The effectiveness and impact of village funds on the development and empowerment of village communities and to find out the extent of the effectiveness of the Village Funds and their impact in the future. The results of the research show that the use of the Village Fund for the 2020 fiscal year is prioritized in the field of village government administration and the field of village community development, but in village development it does not go unnoticed even though in its implementation it uses more village funds (DDS). This study will describe the results of research and discussion based on interviews and field observations about the Effectiveness of Village Fund Allocation Management (ADD) in Village Development in Bagon Village, Puger District, Jember Regency. One of them is that Bagon village is indeed carrying out village development using ADD and DDS appropriately, in which several facilities and infrastructure needed by the community are built to support daily activities such as the construction of asphalt roads, paving roads, road parapets, road parapets and others. other. And this is very beneficial for the people of Bagon village. From there we can see that the effectiveness of managing the allocation of village funds is right on target in accordance with the needs of the Bagon village community, Puger District, Jember Regency. Key words: Management Effectiveness; Allocation of village funds; Village Development;